2019
DOI: 10.1002/cche.10200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenolic compound antioxidant activity in oat varieties using UHPLC–online ABTS and LC Q‐TOF

Abstract: Background and objectives: Phenolic compounds present in oats provide an opportunity for oats to increase its use in the form of functional food. In this study, eight varieties of Australian-grown whole-grain oat were investigated for their phenolic composition and antioxidant potential. Ultra-high-performance liquid chromatography-online 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), coupled with liquid chromatography quadrupole time-of-flight, was used to identify and quantify individual phenolic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Moreover, in this study we report for the first time the content of avenanthramide L (AV_4) in oat sprouts, which is an avenalumic acid substituted avenanthramide, and was increased by 1.9‐fold after oat germination. This avenanthramide has been previously identified in oat grain (Rao et al., 2019), but not in its sprout.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Moreover, in this study we report for the first time the content of avenanthramide L (AV_4) in oat sprouts, which is an avenalumic acid substituted avenanthramide, and was increased by 1.9‐fold after oat germination. This avenanthramide has been previously identified in oat grain (Rao et al., 2019), but not in its sprout.…”
Section: Resultsmentioning
confidence: 58%
“…The phenolic acid profile includes several free phenolic acids previously reported in oat grains and oat sprouts, such as gallic acid, protocatechuic acid, p ‐hydroxybenzoic acid, syringic acid, cinnamic acid, sinapic acid, caffeic acid, p ‐coumaric acid, and ferulic acid (Aborus et al., 2018; Escobedo‐Flores et al., 2018; Multari et al., 2018; Rao et al., 2019; Varga et al., 2018). Interestingly, several phenolic acids were identified in this study for the first time in oat grain and oat sprouts, mainly hydroxycinnamic acids esterified with quinic acid such as sinapoylquinic, coumaroylquinic, and feruloylquinic acids, as well as other derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction procedure followed methodology reported in previous publications [18,19]. Details of phenolic compound composition and antioxidant activity have been reported in References [18,19,40], for rice, oats and barley respectively. Sorghum chemical profile has been reported by Rao, et al [36] and variation with methanol extraction has been reported by Wu, et al [41].…”
Section: Methodsmentioning
confidence: 99%
“…Some phenolic compounds are rare and highly specific to a few cereal grains. Some examples include the 3-deoxyanthocyanin found in sorghum and avenanthramides found in oats [ 23 ]. The biological effects of these phenolic extracts can be attributed to their structure–activity relationships.…”
Section: Cereal Polyphenolsmentioning
confidence: 99%